Development of a checklist for people communicating evidence-based information about the effects of healthcare interventions: a mixed methods study. Issue 7 (21st July 2020) - Oxman, Andrew D; Glenton, Claire; Flottorp, Signe; Lewin, Simon; Rosenbaum, Sarah; Fretheim, Atle
Abstract : Objectives: To make informed decisions about healthcare, patients and the public, health professionals and policymakers need information about the effects of interventions. People need information that is based on the best available evidence; that is presented in a complete and unbiased way; and that is relevant, trustworthy and easy to use and to understand. The aim of this paper is to provide guidance and a checklist to those producing and communicating evidence-based information about the effects of interventions intended to inform decisions about healthcare. Design: To inform the development of this checklist, we identified research relevant to communicating evidence-based information about the effects of interventions. We used an iterative, informal consensus process to synthesise our recommendations. We began by discussing and agreeing on some initial recommendations, based on our own experience and research over the past 20–30 years. Subsequent revisions were informed by the literature we examined and feedback. We also compared our recommendations to those made by others. We sought structured feedback from people with relevant expertise, including people who prepare and use information about the effects of interventions for the public, health professionals or policymakers. Results: We produced a checklist with 10 recommendations. Three recommendations focus on making it easy to quickly determine the relevance of the information and find the key messages. Five recommendations are about helping the reader understand the size of effects and how sure we are about those estimates. Two recommendations are about helping the reader put information about intervention effects in context and understand if and why the information is trustworthy. Conclusions: These 10 recommendations summarise lessons we have learnt developing and evaluating ways of helping people to make well-informed decisions by making research evidence more understandable and useful for them. We welcome feedback for how to improve our advice.